St Peter-On-The-Wall Landscape and heritage on the Essex coast - Dale, Johanna (UCL Press, 2023)
The Chapel of St Peter-on-the-Wall, built on the ruins of a Roman fort, dates from the mid-seventh century and is one of the oldest largely intact churches in England. It stands in splendid isolation on the shoreline at the mouth of the Blackwater Estuary in Essex, where the land meets and interpenetrates with the sea and the sky. This book brings together contributors from across the arts, humanities and social sciences to uncover the pre-modern contexts and modern resonances of this medieval building and its landscape setting. The impetus for this collection was the recently published designs for a new nuclear power station at Bradwell on Sea, which, if built, would have a significant impact on the chapel and its landscape setting. St Peter-on-the-Wall highlights the multiple ways in which the chapel and landscape are historically and archaeologically significant, while also drawing attention to the modern importance of Bradwell as a place of Christian worship, of sanctuary and of cultural production. In analysing the significance of the chapel and surrounding landscape over more than a thousand years, this collection additionally contributes to wider debates about the relationship between space and place, and particularly the interfaces between both medieval and modern cultures and also heritage and the natural environment.